Determining Factors for the Success of Plered Ceramic Exports: A Study on Dodol Badebah - Rhandi Rhiswandi; Dini Fitriani; Alinda S. Nurjanah; Putri Zaharah; Revalina Herdianie (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study investigates the critical determinants of export success in the traditional ceramics industry of Plered, using the Dodol Badebah home enterprise as a case study. The research specifically analyzes the effects of product quality, marketing strategy, and external institutional support on export performance. A quantitative research design was adopted, utilizing structured questionnaires distributed to 60 consumers of Plered ceramics. The data were analyzed using multiple linear regression to assess the influence and significance of each independent variable on export outcomes. Findings indicate that product quality exerts a significant and positive effect on export success, particularly through attributes such as design innovation, material strength, aesthetic value, and compliance with international standards. Conversely, marketing strategy and external support did not demonstrate statistically significant effects, suggesting the need for strategic realignment and more targeted institutional engagement. These results highlight the dominant role of internal capabilities, especially quality control and product development, over external promotional or governmental interventions in driving export readiness and sustainability. The study contributes to the growing body of literature on micro and small enterprises in developing economies by offering empirical evidence on export determinants in cultural and creative industries. Practically, the findings recommend prioritizing product excellence as a core strategy for global market penetration, while simultaneously improving the effectiveness of marketing channels and policy support mechanisms. Future research should explore digital transformation, international consumer preferences, and long-term impacts of policy shifts on export growth in artisanal sectors.